Acceptance of Financial Accounting Information System at Schools : Technology Acceptance Model - Permatasari, Carolina Lita; Prajanti, Sucihatiningsih Dian Wisika (Journal of Economic Education, 2018)
Financial accounting information systems are needed in the presentation of financial statements for the public. Besides that, school management requires accounting information in relation to decision making for organizational purposes, so managerial of accounting information system is needed. One important aspect of accounting that aims to produce financial reporting in an organization is the behavior of financial report managers which become studies of behavioral accounting. The purpose of this study was to examine the effect of perceived ease of use, perceived usefulness, and attitude toward using on behavioral intention to use accounting information systems by school financial managers. This study also aims to determine the extent of the acceptance of accounting information systems by school financial managers in the preparation of financial statements. The method used in this study is a quantitative method with path analysis techniques. The number of population and sample in this study were 50 respondents from an educational foundation in the city of Semarang which consisted of treasurers and the finance department of the Marsudirini Foundation school. The results obtained from this study are the significant influence of perceived ease of use to perceived usefulness; perceived usefulness to attitude toward using; perceived ease of use to attitude toward using; perceived ease of use to behavioral intention to use; and attitude to using toward behavioral intention to use. The rejected hypothesis is the influence of perceived usefulness tobehavioral intention to use.